(Mis)representing Islam the racism and rhetoric of British broadsheet newspapers - Richardson, John E. 1974- (Discourse approaches to politics, society, and culture, 2004)
Explores and illustrates how elite broadsheet newspapers are implicated in the production and reproduction of anti-Muslim racism. This book analyses the centrality of van Dijk's ideological square and the significance and utility of stereotypical topoi in representing Islam and Muslims